Pain upon inserting a peripheral intravenous catheter: Size does not matter - Fredericus HJ van Loon, Wesly H van Aarle, Angelique TM Dierick-van Daele, Arthur RA Bouwman (Vascular Access, 2018)
Background: Approximately 1.2 billion peripheral intravenous catheters are inserted across the world annually. It is known that intravenous cannulation may be a painful procedure, which affects cognitive abilities by increasing anxiety and discomfort. Aim: We hypothesised that inserting a smaller sized peripheral intravenous catheter has a lower level of pain sensation compared to a larger sized catheter. Methods: This observational, cross-sectional study was conducted between May and October 2016, in which surgical patients, aged 18 years or older, were eligible to participate. Experienced anaesthesiologists and nurse anaesthetists routinely obtained peripheral intravenous access according to the standards of care. The primary outcome was pain (verbal numeric rating scale, 0–10) upon intravenous cannulation. Results: A total of 1063 patients were included and they were divided into four groups: group 1, 22 gauge (N = 29); group 2, 20 gauge (N = 447); group 3, 18 gauge (N = 531); and group 4, sized over 18 gauge (N = 56). Inserting an 18-gauge peripheral intravenous catheter resulted in the lowest pain score (3.2 ± 2.0). As a result of the multivariate linear analysis, five factors were significantly associated with pain upon inserting a peripheral intravenous catheter (sex, American Society of Anesthesiology classification, a patient's risk profile on the A-DIVA scale, site of cannulation on the extremity, and whether or not the attempt was successful); however, the size of the inserted peripheral intravenous catheter had no significant relation to the primary outcome. Conclusion: Inserting a smaller sized peripheral intravenous catheter did not result in a lower pain sensation. Moreover, to prevent pain upon inserting a peripheral intravenous catheter, an unsuccessful attempt must be avoided. Keywords: Catheterisation, peripheral, pain, vascular access devices. Date received: 6 January 2017; accepted: 6 November 2017.